1996
DOI: 10.1007/bf02524293
|View full text |Cite
|
Sign up to set email alerts
|

Sterol and steryl ester regulation of phospholipase A2 from the mosquito parasiteLagenidium giganteum

Abstract: Lagenidium giganteum, a facultative parasite of mosquito larvae, cannot synthesize sterols, and requires an exogenous source of these lipids in order to enter its reproductive cycle. This parasite grows vegetatively in the absence of sterols, but requires cholesterol or structurally related compounds to produce motile zoospores, which are the only stage capable of infecting mosquitoes. Sterols structurally related to cholesterol and some steryl esters inhibited the activity of L. giganteum phospholipase A2 (PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…The addition of chol to both types of PCs (PCs/chol: 80/20, 66/34, and 50/50 mol/mol) also exerted an inhibitory effect on the activity of the PLA 2 (Figure ). This result is in agreement with the work of Kerwin et al, who reported that sterol and steryl derivatives selectively inhibited PLA 2 from bovine pancreas, snake venom, and human cytoplasmic 85-kDa PLA 2 . Cholesterol induced a concentration-dependent inhibition of PLA 2 activity in POPC/chol mixtures where the enzymatic activity was decreased to 73%, 40%, and 24% at 150, 300, and 600 nmol chol, respectively.…”
Section: Resultssupporting
confidence: 93%
“…The addition of chol to both types of PCs (PCs/chol: 80/20, 66/34, and 50/50 mol/mol) also exerted an inhibitory effect on the activity of the PLA 2 (Figure ). This result is in agreement with the work of Kerwin et al, who reported that sterol and steryl derivatives selectively inhibited PLA 2 from bovine pancreas, snake venom, and human cytoplasmic 85-kDa PLA 2 . Cholesterol induced a concentration-dependent inhibition of PLA 2 activity in POPC/chol mixtures where the enzymatic activity was decreased to 73%, 40%, and 24% at 150, 300, and 600 nmol chol, respectively.…”
Section: Resultssupporting
confidence: 93%